From the scattered individuality to the great type. Problem of decadence and Self-construction in Nietzsche’s thought. (Nóema, 2013)
The essay investigates the problem of Self-construction in latest Nietzsche’s thought and its relation with the question of decadence. The identity crisis of Western civilisation, the break-up of the ethical and cultural ground of modern European societies, become at the same time the opportunity for a radical renewal of humanity, the starting point for a great «anthropotechnical experiment» aimed at shaping a new human «type», a new model for a Post-Christian ethos.
Keywords: Nietzsche; decadence; type; anthropotechnics; embodiment; Self; asceticism; transfiguration; superman